Participation in and Completion of Vocational Educational and Training for People with Disability - Mavromaras, K; Polidano, C (My University, 2010)
Improving the educational outcomes of people with a disability is seen as key in helping improve their employment and life prospects. Vocational Education and Training (VET) is an important avenue for further education for people with disability because it is a highly flexible and accessible form of education. This paper uses the HILDA survey and multivariate estimation to examine whether people with disability face barriers in participating in and completing a VET qualification, with particular focus on the role of social support. Overall, we find that people with disability are not disadvantaged in terms of participation, but are in terms of completion, especially those with more limiting conditions and those with mental health problems who have low levels of social support. These findings add to the growing literature on the role of social support in the functioning of people with mental illness and underline the importance of ensuring access to adequate support services.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Health; Education and Training; Health -- Disability; Learning, education and training; Health and wellbeing; Health; Education and Training; Disability; Learning, education and training; Health and wellbeing